2019
DOI: 10.4102/ojvr.v86i1.1674
|View full text |Cite
|
Sign up to set email alerts
|

Climatic and regional antibiotic resistance patterns of Staphylococcus aureus in South African dairy herds

Abstract: South Africa is a large country of approximately 1.22 million km 2 , made up of nine provinces with three climatic zones. Farming in the country is mostly defined by regional differences. Of the different organisms isolated from milk samples of dairy cows, Staphylococcus aureus poses a challenge to maintain udder health and wholesome dairy products for human consumption. Antibiotic resistant bacteria are therefore a potential health hazard. The objective of this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 20 publications
2
11
0
2
Order By: Relevance
“…isolates, with respective resistances to penicillin (56.7%), oxacillin (46.7%) and erythromycin (26.7%). [12] evaluating the patterns of antibiotic resistance of S. aureus in dairy herds in South Africa, observed a higher prevalence of resistance to penicillin G and ampicillin, probably due to the fact that these antibiotics of the beta-lactam class are the most used as intramammary remedies in that country. Although a high level of clindamycin-resistant isolates has been observed, few studies have reported this resistance.…”
Section: Resultsmentioning
confidence: 99%
“…isolates, with respective resistances to penicillin (56.7%), oxacillin (46.7%) and erythromycin (26.7%). [12] evaluating the patterns of antibiotic resistance of S. aureus in dairy herds in South Africa, observed a higher prevalence of resistance to penicillin G and ampicillin, probably due to the fact that these antibiotics of the beta-lactam class are the most used as intramammary remedies in that country. Although a high level of clindamycin-resistant isolates has been observed, few studies have reported this resistance.…”
Section: Resultsmentioning
confidence: 99%
“…This could be attributable to the SCC being more of an indicator of irritation and severity of the infection rather than an indicator of antibiotic resistance of the organism. The study on maltose-positive S. aureus [ 18 ] indicated that the lowest prevalence of antibiotic resistance to most categories of antibiotics tested was present in KwaZulu-Natal during spring, except for cephalosporins, holding the lowest levels of prevalence of bacterial resistance in Gauteng during winter [ 18 ]. A possible reason for lower prevalence of antibiotic resistance of S. aureus to cephalosporins during winter in Gauteng may be that the dry cold season has generally a lower probable prevalence of intramammary infections that would require less treatment [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study on maltose-positive S. aureus [ 18 ] indicated that the lowest prevalence of antibiotic resistance to most categories of antibiotics tested was present in KwaZulu-Natal during spring, except for cephalosporins, holding the lowest levels of prevalence of bacterial resistance in Gauteng during winter [ 18 ]. A possible reason for lower prevalence of antibiotic resistance of S. aureus to cephalosporins during winter in Gauteng may be that the dry cold season has generally a lower probable prevalence of intramammary infections that would require less treatment [ 18 ]. This would be supported by the occurring higher average incidence of frost duration in Gauteng [ 19 ], which would have suppressed insect vectors associated in mastitis pathogen transmission [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seasonal difference in AMR was also observed in a study by Watson et al (2012) that found significant increases in shedding of antimicrobial resistant E. coli in May and August in comparison to November. Karzis et al (2019) showed seasonal variations in the prevalence of Staphylococcus aureus antibiotic resistance in South African dairy herds over an 11-year study period where a higher prevalence of antibiotic resistance of S. aureus to cephalosporins was observed during the rainy and muddy season in comparison to the dry season. Overall, seasonal variation in AMR could be caused by many factors, such as the seasonal variation of infectious diseases, differences in management practices, weather conditions, seasonal differences between geographical region, or differences in antibiotic prescription patterns, all of which influence the dynamic interaction between host and environment and can exert antibiotic selective pressure.…”
Section: Prevalence Of E Coli Resistance Across Seasonsmentioning
confidence: 97%